An investigation on the impacts of budgets and budgetary controls on profitability of an organization: case of Marsh Zimbabwe private limited - Chihururu, Tafadzwa Lennon (Midlands State University, 2017)
The study sought to investigate the impacts of budgets and budgetary controls on the profitability of Marsh Zimbabwe Private Limited. The increase in the use of budgetary controls to attain profits have moved Marsh Zim (Pvt) Ltd to implement budgetary controls and move away from just a mere operation without budgetary control methods. As a result, it is the objective of this study to investigate the impacts of budgetary control on the operational and financial performance (profitability) of Marsh Zim (Pvt) Ltd. The researcher used the mixed approach research design to collect data and primary data was collected through the use of interviews and questionnaires. Four departments of Marsh Zim (Pvt) Ltd were used to draw the population sample and stratified random sampling technique was used. The results showed that the use of budgetary controls created several benefits, which included the operational performance, workers motivation and an improvement in the coordination of workers. However, these benefits were outweighed by the increase in expenditure, operating costs as well as the decline in the profitability from period 2013-2015. The implementation of budgetary controls did not improve the profitability of Marsh Zim (Pvt) Ltd as expected. Based on the results obtained, the researcher recommended that Marsh Zim (Pvt) Ltd should adopt the use of flexible budgetary controls, also the use of budget software’s and the budgetary control techniques, which include strategic management, in-depth variance analysis and forecast.